Cognition, depression, and functional health profiles (CoDe-F) of non-debilitated aged in the coastal belt of southern India: An explorative study at homes for the aged - Anil Raj Assariparambil; Judith Angelitta Noronha; H. Manjunatha Hande; Elsa Sanatombi Devi; Vani Lakshmi R; Anice George (Elsevier, 2024)
Introduction: Cognitive function, depression, and functional health profiles of older adults directly predict overall well-being. Family dynamics in India are changing mainly due to urbanization, migration of the younger generation for education or employment, and change in the social system, making the elderly parents alone and slowly getting transferred to old age homes. Hence, the investigators were interested in determining the functional health, depression, and cognitive decline among young and middle-aged non-debilitated institutionalized older adults. Objectives: To determine the correlation between cognitive function and depression among the young-old and old-old elderly and determine the functional health profiles of non-debilitated older adults residing at the old age homes of the coastal part of southern India. Study design: An exploratory study at the homes for the aged. Methodology: The survey was conducted at old age homes after obtaining permission from the respective authorities. Socio-demographic proforma, functional health profiles, Modified Barthel Index, Short-form depression scale, and Muscle strength assessments were the data collection instruments. Statistical Analysis was done through Jamovi. (Version 2.3). Descriptive statistics and Karl Pearson's parametric statistic test were applied. Results: Montreal's cognitive assessment revealed that 81% of the elderly had borderline cognitive impairment. The short-form geriatric depression score revealed that 87% reported mild depressive symptoms. As cognitive ability declined, depressive symptoms were common among institutionalized older adults (r = −0.494, p < 0.05) Conclusion: Depression, cognitive impairment, and functional health profiles of older adults residing at old age homes need to be monitored regularly, and appropriate interventions must be employed to improve their quality of life.